Effect of double aging treatment on the tribological properties of 15-5PH coating on 17-4PH stainless steel by laser cladding - Hongxi Chen; Yanbin Du; Qiang Liang; Wensheng Ma; Jian Tu (Journal of Materials Research and Technology)
To enhance the wear resistance of 17-4PH stainless steel, 15-5PH coatings are initially applied to its surface utilizing laser cladding technology. Subsequently, a double aging treatment is implemented as a post-processing method to further improve its surface properties. The effects of both the first and second aging processes on the phase, microstructure, microhardness, and wear resistance of the cladded layer are investigated. The results indicate that both aged (AG) and double-aged (DG) structures are primarily composed of α and γ phases, accompanied by the formation of FeCr0.29Ni0.16C0.06 and Cr₂Fe₁₄C. The AG structure predominantly consists of elongated plate-like martensite, with numerous larger, irregular black carbides present. In contrast, The DG structure is characterized mainly by short rod-like or droplet-shaped martensite exhibiting a network structure; many fine silvery white carbides precipitate along the grain boundaries. The double-aging treatment exhibits the highest average microhardness, which is 35.26% higher compared to 17-4PH. Evaluations concerning friction coefficient, wear volume, wear tracks, relative wear resistance, and improvement rate reveal that DG exhibits superior wear resistance compared to other treatments. The COF of DG is the lowest at 0.717, which results in a 64.03% reduction in wear loss compared to 17-4PH. The wear mechanisms of DG are primarily adhesive wear and oxidative wear. These findings significantly enhance our understanding of material performance under tribological conditions and provide valuable insights for improving the wear resistance of 17-4PH components.